Improving The Problem Solving Skill Through Metacognitive Strategies Assisted by Student Worksheets - Johan Syahbrudin; Anita Anggraini (Journal of Educational Science and Technology (EST), 2019)
This study aims to investigate the effectiveness of metacognitive learning strategy assisted by student worksheets based on troubleshooting even though only for a short amount of time to develop students' physics problem solving abilities. This research design using quasi-experiment design. The study population was students of class XI MAN Yogyakarta 1 with two sample classes totaling 53 people taken through cluster random sampling techniques. Collecting research data through study documentation, observation, and tests. Analysis of research data using descriptive analysis techniques and quantitative analysis (independent sample t-test). This study shows the results that the application of metacognition learning strategy assisted by student worksheets based on troubleshooting in a relatively short period of time is not effective to produce physics problem solving abilities.